Aggregation of Zoospores on Sharklet Microtopographic Surfaces - Nguyen, Nhung Thi Thuy; Hoang, Trinh Xuan (Communications in Physics, 2021)
Surfaces with engineered microtopographies are potential candidate against biofouling to replace the use of biocides in the marine environment. Understanding the antifouling mechanism of microtopographic surfaces against marine microorganisms, however, has been limited. In this work, we theoretically studied the aggregation of Ulva linza zoospores on the Sharklet topographic surfaces by employing the extended Surface Energetic Attachment (SEA) model proposedin a previous work. The energy parameters of the model were obtained by matching theoretical results with experimental data for one type of Sharklet surface. Monte Carlo simulations were then carried out for a series of Sharklet surfaces with various numbers of distinct features. Inagreement with prior experimental results, our simulations indicate that engineered topographies promote smaller aggregates than those on a smooth surface. Furthermore, we show that the maximum effect of the Sharklet topography on the aggregate size of U. linza can be obtained with just 3 distinct features.